Arctic Environmental Test of Flame Equipment. - ARMY TEST AND EVALUATION COMMAND ABERDEEN PROVING GROUND MD (1970)
The environmental test procedure describes test methods and techniques for evaluating the performance and characteristics of flame equipment under Arctic winter environmental conditions. The evaluation is related to criteria established by applicable qualitative materiel requirements (QMR), small development requirements (SDR), technical characteristics (TC), or other appropriate design requirements and specifications.